Impaired ion channel function related to a common KCNQ1 mutation: implications for risk stratification in long QT syndrome 1 - Aidery, Parwez; Kisselbach, Jana; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Gene, 2012)
Long QT syndrome (LQTS) 1 is the most common type of inherited LQTS and is linked to mutations in the KCNQ1 gene. We identified a KCNQ1 missense mutation, KCNQ1 G325R, in an asymptomatic patient presenting with significant QT prolongation (QTc, 448-600ms). Prior clinical reports revealed phenotypic variability ranging from the absence of symptoms to syncope among KCNQ1 G325R mutation carriers. The present study was designed to determine the G325R ion channel phenotype and its association with the clinical LQTS presentation. Electrophysiological testing was performed using the Xenopus oocyte expression system. KCNQ1 G325R channels were non-functional and suppressed wild type (WT) currents by 71.1%. In the presence of the native cardiac regulatory ß-subunit, KCNE1, currents conducted by G325R and WT KCNQ1 were reduced by 52.9%. Co-expression of G325R and WT KCNQ1 with KCNE1 shifted the voltage-dependence of I(Ks) activation by 12.0mV, indicating co-assembly of mutant and WT subunits. The dysfunctional biophysical phenotype validates the pathogenicity of the KCNQ1 G325R mutation and corresponds well with the severe clinical presentation revealed in some reports. However, the index patient and other mutation carriers were asymptomatic, highlighting potential limitations of risk assessment schemes based on ion channel data.
Gesehen am 05.04.2018